Peran Kepuasan Dalam Memediasi Pengaruh Customer Experience, Word Of Mouth Dan Kualitas Layanan Mobile Banking Terhadap Loyalitas Nasabah - Vika Nur Safitri; Emy Widyastuti (Al-bank: Journal of Islamic Banking and Finance, 2023)
This study aims to analyze the role of satisfaction in mediating the relationship between Customer Experience (CE), Word Of Mouth (WoM) and Mobile Banking Service Quality (SQ) with Customer Loyalty. The research method uses associative descriptive quantitative by analyzing secondary data in the form of questionnaires. The population is Bank Syariah Indonesia sub-branch office Kudus customers and a sample of 100 respondents determined by purposive sampling technique. The results showed that loyalty can be influenced by CE positively but not significantly, influenced by WoM positively significant and influenced by SQ negatively insignificant. Furthermore, the satisfaction variable is influenced by CE positively but insignificantly, influenced by WoM positively significantly and influenced by SQ negatively insignificantly. In testing Z against Y, a significant relationship with a positive direction was found. Furthermore, the role of satisfaction as a mediator is only able to mediate the effect of WoM on loyalty